2019
DOI: 10.5688/ajpe7365
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Approach to Intentional Interprofessional Experiential Education at a Non-Academic Community Hospital

Abstract: Objective. To develop and implement a multimodal structured approach to intentional interprofessional experiential education at a non-academic community hospital, and to evaluate students' perceptions of the program. Methods. A multimodal structured approach to intentional interprofessional experiential education was designed that consisted of medical and pharmacy students participating together in daily prerounds, daily teaching rounds, and once or twice weekly lunch-and-learn sessions at a non-academic commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
(35 reference statements)
0
15
1
Order By: Relevance
“…This programme provides these students with opportunities to learn about each other's training and roles on the team and to engage in peer teaching. Contrary to the authors' finding, it has been reported in the US that most pharmacy and medical students appeared to better perceive the value of working together with other healthcare professions students on enhancing their knowledge and ability to work on an interdisciplinary team upon graduation (Nwaesei et al, 2019).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This programme provides these students with opportunities to learn about each other's training and roles on the team and to engage in peer teaching. Contrary to the authors' finding, it has been reported in the US that most pharmacy and medical students appeared to better perceive the value of working together with other healthcare professions students on enhancing their knowledge and ability to work on an interdisciplinary team upon graduation (Nwaesei et al, 2019).…”
Section: Discussioncontrasting
confidence: 96%
“…This finding is a serious concern that needs to be addressed urgently in order for the Nigerian healthcare professionals' education to be in tune with global best practice of an increasing collaboration of healthcare providers to optimise patients' health (Auta, Strickland-Hodge & Maz, 2016). In the US, both pharmacy students and medical students are required to participate in the inter-professional experiential education (IPE) programme together, to fulfil accreditation standards for both pharmacy and medical education (Nwaesei et al, 2019). This programme provides these students with opportunities to learn about each other's training and roles on the team and to engage in peer teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies focused on interprofessional rounds, 21,22,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] of which 9 studies were either medium or highquality (Table 3). Reported benefits of this practice included a perceived increase in collaboration 22,62,65 and communication 21,22,57,60,65,66 among health care teams; a highquality time series study also reported earlier discharge times.…”
Section: Interprofessional Roundsmentioning
confidence: 99%
“…Interprofessional rounds may improve team collaboration and communication, and enhance discharge planning. 21,22,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] Moderate confidence…”
Section: Studies Contributing To the Review Findingmentioning
confidence: 99%
See 1 more Smart Citation